1994
DOI: 10.1128/mcb.14.7.4522-4531.1994
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 Is a Glucose-Regulated Transcription Factor Whose Leucine-Rich Repeat Binds Several Proteins Important for Placing CCR4 in Its Proper Promoter Context

Abstract: The yeast CCR4 protein is required for the expression of a number of genes involved in nonfermentative growth, including glucose-repressible ADH2, and is the only known suppressor of mutations in the SPT6 and SPT10 genes, two genes which are believed to be involved in chromatin maintenance. We show here that although CCR4 did not bind DNA under the conditions tested, it was able to activate transcription when fused to a heterologous DNA-binding domain. The transcriptional activation ability of CCR4, in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Recently two additional proteins, Ccr4p and Hpr1p, have been found in the Paf1p/Cdc73p-containing complex (Chang and Jaehning, unpublished observations). Both Ccr4p and Hpr1p affect transcription of subsets of yeast genes and neither is found in the Srbp-containing holoenzyme (45,46). The composition of this second biochemically distinct form of the pol II holoenzyme is shown on the right side of Figure 2.…”
Section: The Pol II 'Holoenzyme(s)'mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently two additional proteins, Ccr4p and Hpr1p, have been found in the Paf1p/Cdc73p-containing complex (Chang and Jaehning, unpublished observations). Both Ccr4p and Hpr1p affect transcription of subsets of yeast genes and neither is found in the Srbp-containing holoenzyme (45,46). The composition of this second biochemically distinct form of the pol II holoenzyme is shown on the right side of Figure 2.…”
Section: The Pol II 'Holoenzyme(s)'mentioning
confidence: 99%
“…The two holoenzyme complexes are portrayed transcribing overlapping major and minor subsets of genes. This model is based on the fact that some of the SRBs are essential genes shown to affect transcription of most yeast genes (47), while PAF1, CDC73, CCR4 and HPR1, in addition to the shared components GAL11, SIN4 and RGR1, are all non-essential and appear to affect only a subset of transcripts (31,39,43,45,46). The overlapping nature of the effects of the two complexes is based on the fact that expression of some genes is affected by mutations in either complex.…”
Section: The Pol II 'Holoenzyme(s)'mentioning
confidence: 99%
“…A central domain featuring several tandem copies of a leucine‐rich‐repeat (LRR) domain (Malvar et al , 1992) has been reported to interact with yCaf1p (Draper et al , 1995), with other putative components of the core CCR4–NOT complex (Liu et al , 2001) and with potential‐binding ligands of the whole complex. This LRR domain is thus considered to be the link that connects yCcr4p to the remainder of the complex (Draper et al , 1994; Liu et al , 1998) and other ligands, and distinguishes all Ccr4p orthologues from other EEP family members and CCR4‐like proteins (Dupressoir et al , 2001; Chen et al , 2002). The C‐terminal region contains a deadenylase domain characteristic of the exonuclease‐endonuclease‐phosphatase superfamily with conserved catalytic Asp and His residues.…”
Section: Introductionmentioning
confidence: 99%
“…As a highly conserved member of the CCR4–NOT complex, yCcr4p is the major cytoplasmic deadenylase in yeast and acts as the main catalytic component (Chen et al , 2002). Yeast Ccr4p features three major functional domains and has been categorized as a member of the endonuclease‐exonuclease‐phosphatase (EEP) family of proteins through biochemical studies (Draper et al , 1994). The N‐terminal glutamine/asparagine‐rich region is believed to have a transcriptional activation domain that interacts with the transcriptional machinery.…”
Section: Introductionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , the deadenylation process (reviewed in Caponigro & Parker, 1996) is the first step of mRNA degradation. It is achieved by the Ccr4–Not complex (Daugeron et al , 2001; Tucker et al , 2001), a large multi‐protein complex (Liu et al , 1997; Chen et al , 2001), built around a core of seven proteins: the carbon catabolite repressor 4 factor (Ccr4), first identified as a gene expression regulating protein (Denis, 1984), the Pop2 protein, also known as Caf1 (for Ccr4 associated factor 1; Draper et al , 1995) and five Not proteins (Not1–5) required for the proper function of the Ccr4–Not complex (Draper et al , 1994; Liu et al , 1998). Interactions between Ccr4, Pop2 and the Not proteins, together with other proteins present in the Ccr4–Not complex, have been characterized (Benson et al , 1998; Bai et al , 1999; Badarinarayana et al , 2000; Lemaire & Collart, 2000; Liu et al , 1997, 2001).…”
Section: Introductionmentioning
confidence: 99%